Dealing Between Domestic Policy and International Standard on Worker Welfare in MNC’s Operation in Host Country: Case Study in PT. Betts Indonesia - Effendi, Tonny Dian; Kusumaningrum, Demeiati Nur (IJRDO - Journal of Business Management, 2017)
Global capitalism argued that industrialization is a leading sector of growth and prosperity. State policy need to encourage foreign investment and multilateral trade system as the internationalization of economic liberalism. In developing country such as Indonesia, multinational corporation welcome as the government partner on development aimed to reduce unemployment and rise the market export commodities. Whereas, the structuralism accused the multinational corporation as the instrument of hegemon western country that bring the problems of worker welfare and environmental preservation. This paper would like to describe how the United States corporation – Betts Indonesia harmonize the international standard of worker welfare with the government rules of host country. Data and information obtained from library research and depth interviewed to management and worker of Betts Indonesia as the subject of research. It proved the liberal proposition that the corporation support the government rules on the program of worker welfare involve BPJS (Indonesian Social Insurance), the freedom of labor union, pension fee, the right of maternity, and the Corporate Social Responsibility project with PMI (Indonesian National Red Cross) in which the integration of international standard as the corporation own values ruined the claim of structuralism.